Pengaturan SIM terhadap Pengguna Sepeda Listrik - Perdy Pratama; Rosa Tedjabuwana (Universitas Batanghari Jambi, 2025)
This study examines the regulation of driver's licenses (SIM) for electric bicycle users in Indonesia, which are increasingly popular as an environmentally friendly mode of transportation but pose legal and safety challenges due to unclear regulations. Using a normative and legal-legal approach, the study analyzes Law Number 22 of 2009, Minister of Transportation Regulation Number 45 of 2020, and Police Regulation Number 5 of 2021, which stipulate that electric bicycles with speeds up to 25 km/h do not require a driver's license, while those with speeds above 35 km/h require a Class C driver's license. The results indicate a legal vacuum due to regulatory inconsistencies, low user awareness, and inconsistent law enforcement, such as verbal warnings during Operation Zebra Semeru 2024, with 647 electric bicycle accidents recorded between January and June 2024. The study recommends regulatory harmonization, intensive outreach, and strengthening bicycle lane infrastructure to support effective driver's license regulations to improve traffic safety without hindering transportation innovation.